Two-dimensional Cahn-Hilliard simulations for coarsening kinetics of spinodal decomposition in binary mixtures - Koenig, Bjoern; Ronsin, Olivier J. J.; Harting, Jens (Physical Chemistry Chemical Physics, 2021)
The evolution of the microstructure due to spinodal decomposition in phase separated mixtures has a strong impact on the final material properties. In the late stage of coarsening, the system is characterized by the growth of a single characteristic length scale L similar to Ct(alpha). To understand the structure-property relationship, the knowledge of the coarsening exponent alpha and the coarsening rate constant C is mandatory. Since the existing literature is not entirely consistent, we perform phase field simulations based on the Cahn-Hilliard equation. We restrict ourselves to binary mixtures using a symmetric Flory-Huggins free energy and a constant composition-independent mobility term and show that the coarsening for off-critical mixtures is slower than the expected t(1/3)-growth. Instead, we find alpha to be dependent on the mixture composition and associate this with the observed morphologies. Finally, we propose a model to describe the complete coarsening kinetics including the rate constant C.
CRIS-Team WoS Importer:2021-11-12